Hubungan Intensitas Melihat Instagram Story dan Intensitas Komunikasi Antar Pengguna dengan Perilaku Mengunggah Instagram Story - Reyuni Adelina Br Barus; Hedi Pudjo Santoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The presence of the latest Instagram feature, the Instagram Story was able to attract the attention of its users from various circles. Instagram users are now competing to share their daily activities through this feature. Instagram Story is a sign that new media is able to create new behavior for its users and personal things became public consumption. The communication formed also becomes more complex than the direct interpersonal communication. The purpose of this research is to know the relation of intensity view Instagram Story and intensity of communication between user with behavior of uploading Instagram Story. Sampling in this research using purposive sampling. The population in this research were 18-35 year olds who were active users of Instagram. The number of samples researched were 50 respondents.Based on the hypothesis test conducted by Kendall's Tau-b correlation analysis, it shows that: first, there is a correlation between intensity view Instagram Story and behavior of uploading Instagram Story with significance value 0.000. It shows that there is a very significant relationship between the intensity of viewing Instagram Story and behavior of uploading Instagram. Second, there is a correlation between the intensity of communication between users and the behavior of uploading Instagram Story with a significance value of 0,000. It shows that there is a very significant relationship between the intensity of communication between users and the behavior of uploading Instagram. Advice given that the user should be more aware of the importance of understanding in sorting out things that are eligible to be published or not in social media, especially Instagram Story.